AERODYNAMICS OF THE BIPLANE MODULE OF VETROCOLES - Павловський, P. M.; Ударцев, Є. П.; Орлов, М. А. (Proceedings of National Aviation University (archive), 2020)
The results of experimental research of the model of the bi-planetary module of a Dyryk rotor windrower in the industrial AT-1 aerodynamic tube ANTK them are presented. O.K. Antonov The advantage of the biplane arrangement of the traction module over the insulated wing is shown, which allows to reduce the size of the wind power plant at equal power